Integrating working memory capacity and context-processing views of cognitive control. - Redick, Thomas S.; Engle, Randall W. (Quarterly Journal of Experimental Psychology, 2011)
Individuals low in working memory capacity (WMC) exhibit impaired performance on a variety of cognitive control tasks. The executive-attention theory of WMC (Engle & Kane, [2004[) accounts for these findings as failures of goal maintenance and response conflict resolution. Similarly, the context-processing view (Braver et al., [2001]) provides an explanation of cognitive control deficits observed in schizophrenia patients and older adults that is based on the ability to maintain context information. Instead of maintenance deficits, the inhibition view (Hasher, Lustig, & Zacks, [2007]) states that older adults and individuals low in WMC primarily have an impairment in the ability to inhibit information. In the current experiment, we explored the relationships among these theories. Individuals differing in performance on complex span measures of WMC performed the AX-Continuous Performance Test to measure context-processing performance. High-WMC individuals were predicted to maintain the context afforded by the cue, whereas low-WMC individuals were predicted to fail to maintain the context information. Low-WMC individuals made more errors on AX and BX trials and were slower to respond correctly on AX, BX, and BY trials. The overall pattern of results is most consistent with both the executive-attention and context-processing theories of cognitive control. Reprinted by permission of the publisher.